Association of subjective global assessment of nutritional status with gut microbiota in hemodialysis patients: a case–control study. Issue 6 (2nd April 2020) - Lin, Ting-Yun; Hung, Szu-Chun
Abstract: Background: Protein-energy wasting (PEW) is prevalent and associated with adverse outcomes in patients with chronic kidney disease (CKD). However, the pathogenesis of PEW in CKD patients has not been fully identified. The gut microbiota has been implicated in the regulation of host metabolism and energy balance. Therefore, we aimed to explore the association between nutritional status and the composition of the gut microbiota in hemodialysis patients. Methods: Gut microbial diversity and taxonomy were examined in 88 hemodialysis patients with PEW ( n = 22) and normal nutritional status ( n = 66) who were matched 1:3 for age and sex. Nutritional status was assessed by using the 7-point subjective global assessment (SGA) score (1–3 = severe PEW; 4–5 = moderate PEW and 6–7 = normal nutrition). The gut microbiota was assessed by 16S ribosomal RNA gene sequencing. Results: Patients with normal nutritional status had a significantly higher body mass index and physical activity and serum albumin levels, but significantly lower levels of inflammatory cytokines than patients with PEW. The most striking finding was that the α -diversity of the gut microbiota was significantly lower in patients with PEW. In a multivariate analysis, the SGA score was independently and positively associated with α -diversity (P = 0.049). Patients with or without PEW were different with respect to the principal coordinate analysis of β -diversity. Notably, the relative abundance of Faecalibacterium prausnitzii, a butyrate-producing bacteria, was markedly reduced in patients with PEW. Conclusion: In hemodialysis patients, PEW assessed with the SGA was associated with gut dysbiosis.